2021
DOI: 10.1108/cg-11-2019-0355
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of corporate governance and agency control: the effectiveness of mechanisms in creating value for companies with IPO on the Brazilian stock exchange

Abstract: Purpose From the agency theory’s point of view, this paper aims to analyze corporate governance mechanisms about the characteristics of the companies quoted in the segments Bovespa Mais and Bovespa Mais 2 and their influence on the creation of value in preparation for the opening of the initial public offering (IPO). Design/methodology/approach A quantitative approach was adopted to achieve the proposed objective using the panel data with fixed effects and secondary data collected on the Comissão de Valores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 234 publications
(220 reference statements)
1
9
0
Order By: Relevance
“…The most relevant part of this system is the presence of a dynamic and coherent board of directors (Saleem et al , 2021). Boards have a potentially critical role to play in mitigating agency problems (Fama, 1980; Jensen and meckling, 1976; Aslam and Haron, 2021; Barros et al , 2021), designing and implementing strategy and fostering links between the firm and its external environment (Arora and Bodhanwala, 2018). The board of directors bears the ultimate responsibility for the tax affairs of the company (Nadeem et al , 2017) and is held accountable for them by shareholders and other stakeholders (Zemzem and Ftouhi, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The most relevant part of this system is the presence of a dynamic and coherent board of directors (Saleem et al , 2021). Boards have a potentially critical role to play in mitigating agency problems (Fama, 1980; Jensen and meckling, 1976; Aslam and Haron, 2021; Barros et al , 2021), designing and implementing strategy and fostering links between the firm and its external environment (Arora and Bodhanwala, 2018). The board of directors bears the ultimate responsibility for the tax affairs of the company (Nadeem et al , 2017) and is held accountable for them by shareholders and other stakeholders (Zemzem and Ftouhi, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, current CG thinking and practices favour the employment of structural mechanisms to mitigate agency problems that influence organisational performance (Boivie et al , 2016; de Barros et al , 2021; Goodman et al , 2021; Muchemwa et al , 2016; Tshipa et al , 2018). Indeed, one of the consequences of agency theory-based uncertainty between principals and agents is goal conflict.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, this factor is popularly used as an indicator of a firm's internal governance to prevent conflicts of interest between managers and shareholders (Chiang and He, 2010). Hence, firms with high board independence tend to implement appropriate policies, leading to improved WCM efficiency and, eventually, firm performance, based on agency theory (Chong et al, 2018;Duppati et al, 2019;Barros et al, 2021). Additionally, Fiador (2016) found that more non-executive directors in boards reduced CCC and AR periods.…”
Section: Board Independencementioning
confidence: 99%